A Euryhaline‐Fish‐Inspired Salinity Self‐Adaptive Nanofluidic Diode Leads to High‐Performance Blue Energy Harvesters. Issue 31 (29th June 2022) - Hao, Junran; Bao, Bin; Zhou, Jiajia; Cui, Yanshuai; Chen, Xiachao; Zhou, Jiale; Zhou, Yahong; Jiang, Lei
Abstract: The adaptability to wide salinities remains a big challenge for artificial nanofluidic systems, which plays a vital role in water–energy nexus science. Here, inspired by euryhaline fish, sandwich‐structured nanochannel systems are constructed to realize salinity self‐adaptive nanofluidic diodes, which lead to high‐performance salinity‐gradient power generators with low internal resistance. Adaptive to changing salinity, the pore morphology of one side of the nanochannel system switches from a 1D straight nanochannel (45 nm) to 3D network pores (1.9 nm pore size and ≈10 13 pore density), along with three orders of magnitude change for charge density. Thus, the abundant surface charges and narrow pores render the membrane‐based osmotic power generator with power density up to 26.22 Wm −2 . The salinity‐adaptive membrane solves the surface charge‐shielding problem caused by abundant mobile ions in high salinity and increases the overlapping degree of the electric double layer. The dynamic adaption process of the membrane to the hypersaline environment endows it with good salt endurance and stability. New routes for designing nanofluidic devices functionally adaptable to different salinities and building power generators with excellent salt endurance are demonstrated. Abstract : A sandwich‐structured nanochannel system is constructed to realize salinity self‐adaptive nanofluidic diodes, which lead to a high‐performance salinity‐gradient power generator with low internal resistance. Adaptive to changing salinity, the pore morphology of one side of the nanochannel system switches from a 1D straight nanochannel to 3D network pores, along with three orders of magnitude change for charge density.